The vandermonde matrix and its applications - 517931 Muna Maryam Azmy; Ali Abd. Rahman; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2010